Description of Pseudingolfiella possessionis n. sp. (Crustacea, Amphipoda) from sub-Antarctic Île de La Possession, Crozet archipelago: the second freshwater amphipod known from the Antarctic biome, a human introduction of Gondwanan ancestry? - Smet, Willem H. De (Zootaxa, 2015)
A new species of freshwater amphipod, Pseudingolfiella possessionis n. sp. (Senticaudata, Pseudingolfiellidae), is described from the submerged moss vegetation of small brooklets at sub-Antarctic Île de La Possession, Crozet archipelago. It constitutes the second freshwater amphipod species known for the sub-Antarctic and Antarctic region, and the fourth member of the genus. The main characters distinguishing it from all congeners are: the spine on the posterior margin of the dactylus, incisor and lamina mobilis of mandible each with 5 teeth, the setation of the maxilliped, the vestigial second article of pleopod 3 in the female, the undulate and laterally notched posterolateral margin of the external ramus of uropods 1 and 2 in the male, the spinulate dorsomedian projection of the telson.